2016
DOI: 10.15252/embj.201593360
|View full text |Cite
|
Sign up to set email alerts
|

Global RNA recognition patterns of post‐transcriptional regulators Hfq and CsrA revealed by UV crosslinking in vivo

Abstract: The molecular roles of many RNA‐binding proteins in bacterial post‐transcriptional gene regulation are not well understood. Approaches combining in vivo UV crosslinking with RNA deep sequencing (CLIP‐seq) have begun to revolutionize the transcriptome‐wide mapping of eukaryotic RNA‐binding protein target sites. We have applied CLIP‐seq to chart the target landscape of two major bacterial post‐transcriptional regulators, Hfq and CsrA, in the model pathogen Salmonella Typhimurium. By detecting binding sites at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
356
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 285 publications
(377 citation statements)
references
References 135 publications
(200 reference statements)
17
356
2
2
Order By: Relevance
“…Salmonella enterica was reported to somehow activate expression of the uvrY ortholog, sirA, via cAMP-CRP, with positive downstream effects on csrB-lacZ and csrC-lacZ gene fusions (79). In addition, CLIP-seq studies in Salmonella revealed binding of CsrA to crp (cap) leader mRNA at two locations (80), one of which is related in sequence to E. coli BS2 (Fig. 8A).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella enterica was reported to somehow activate expression of the uvrY ortholog, sirA, via cAMP-CRP, with positive downstream effects on csrB-lacZ and csrC-lacZ gene fusions (79). In addition, CLIP-seq studies in Salmonella revealed binding of CsrA to crp (cap) leader mRNA at two locations (80), one of which is related in sequence to E. coli BS2 (Fig. 8A).…”
Section: Discussionmentioning
confidence: 99%
“…Peaks were called using JAMM (joint analysis of next-generation sequencing replicates via mixture model clustering) (Ibrahim et al 2015) and PEAKachu (Holmqvist et al 2016). JAMM was designed to report a large number of peaks and relies on external post-processing for peak filtering.…”
Section: Methodsmentioning
confidence: 99%
“…One example is the malM 3 ′ UTR, which associates with both Hfq and ProQ via overlapping binding sites (Holmqvist et al 2016;E Holmqvist, in prep.). Given their shared target, the question naturally arises whether ProQ might also interact with Hfq, either through a protein-protein interaction or an RNA-mediated interaction.…”
Section: Proq May Exclude Hfq From Binding To Shared Rna Targetsmentioning
confidence: 99%